62=(3x-5)+3x+(4x+2)

Simple and best practice solution for 62=(3x-5)+3x+(4x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 62=(3x-5)+3x+(4x+2) equation:


Simplifying
62 = (3x + -5) + 3x + (4x + 2)

Reorder the terms:
62 = (-5 + 3x) + 3x + (4x + 2)

Remove parenthesis around (-5 + 3x)
62 = -5 + 3x + 3x + (4x + 2)

Reorder the terms:
62 = -5 + 3x + 3x + (2 + 4x)

Remove parenthesis around (2 + 4x)
62 = -5 + 3x + 3x + 2 + 4x

Reorder the terms:
62 = -5 + 2 + 3x + 3x + 4x

Combine like terms: -5 + 2 = -3
62 = -3 + 3x + 3x + 4x

Combine like terms: 3x + 3x = 6x
62 = -3 + 6x + 4x

Combine like terms: 6x + 4x = 10x
62 = -3 + 10x

Solving
62 = -3 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
62 + -10x = -3 + 10x + -10x

Combine like terms: 10x + -10x = 0
62 + -10x = -3 + 0
62 + -10x = -3

Add '-62' to each side of the equation.
62 + -62 + -10x = -3 + -62

Combine like terms: 62 + -62 = 0
0 + -10x = -3 + -62
-10x = -3 + -62

Combine like terms: -3 + -62 = -65
-10x = -65

Divide each side by '-10'.
x = 6.5

Simplifying
x = 6.5

See similar equations:

| (2x+1)(ax+b)=6x^2-5x^2+c | | 2(3x-7)=6(5+9)+4 | | -7=1/5x | | 4ax+b=12bx+40b | | 4/5x^2y,8/3xy,12/13xy^5 | | 2(5x-1)=8(x+1) | | 2x^2+3x+j=0 | | 7t^2-112= | | 3y-1=2y-5 | | n=3.64+12 | | 60x^3+24x^2-360x-144= | | 3y+5-7y-7= | | 30x-15x=150 | | -11+x=4 | | 25k^2+81= | | -5/0 | | 4x+12=x+14-12 | | 9r^2+30r+25= | | x^2-64=12x | | 2sin(2x-1)=0 | | 4x+12=x+14 | | 3/5-4/5 | | 21=-3/8× | | x=.6+384 | | 2x+3=5x+97 | | 7=-7/5x-7 | | y=-7/5(-5)-7 | | 64c^2-25t^2= | | 73/5-4/5 | | y=-7/5(0)-7 | | y=-7/5x-7 | | 4=x*7+86/2 |

Equations solver categories